ПРОТИПРАВНА ПІДПРИЄМНИЦЬКА ДІЯЛЬНІСТЬ ЯК ФАКТОР ЗАГРОЗИ ЕКОНОМІЧНІЙ БЕЗПЕЦІ УКРАЇНИ - Попова, Лілія Миколаївна (SUPREMANCE OF LAW, 2017)
In this article the author examines the issue of ensuring the economic security of entrepreneurial activity in Ukraine and examines the main types of violations of economic legislation. The author defines the factors constraining the economic development of the country and indicates the main features that determine economic security. In the article, the author emphasizes that the economic security of any state and individual business entities is impossible without a system of compliance with legislation in the field of economic policy. In addition, the author suggests ways to increase legal liability for committing economic crimes.